2003
DOI: 10.1351/pac200375020375
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate-independent methylerythritol phosphate pathway for isoprenoid biosynthesis. Elucidation and distribution

Abstract: A long-overlooked metabolic pathway for isoprenoid biosynthesis, the mevalonateindependent methylerythritol phosphate (MEP) pathway, is present in many bacteria and in the chloroplasts of all phototrophic organisms. It represents an alternative to the well-known mevalonate pathway, which is present in animals, fungi, plant cytoplasm, archaebacteria, and some eubacteria. This contribution summarizes key steps of its elucidation and the state-ofthe-art knowledge of this biosynthetic pathway, which represents a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 72 publications
2
103
1
3
Order By: Relevance
“…In plants, both IDP and DMADP are synthesized via two parallel pathways, the mevalonate (MVA) pathway, which is active in the cytosol, and the methylerythritol 4-phosphate (MEP) pathway, which is active in the plastids (Lichtenthaler, 1999;Rodriguez-Concepció n and Boronat, 2002;Rohdich et al, 2002;Rohmer, 2003). It is generally recognized that the cytosolic pathway is responsible for the synthesis of sesquiterpenes, phytosterols and ubiquinone, whereas monoterpenes, gibberellins, abscisic acid, carotenoids and the prenyl moiety of chlorophylls, plastoquinone and tocopherol are produced in plastids (Lichtenthaler, 1999;Rodriguez-Concepció n and Boronat, 2002;Rohdich et al, 2002;Rohmer, 2003), but indications of cross-talk between the plastidic and cytosolic pathways have been found in tobacco, Arabidopsis and snapdragon petals Dudareva et al, 2005;Ohara et al, 2003). The direct precursors of terpenoids, linear geranyl diphosphate (GDP, C 10 ), farnesyl diphosphate (FDP, C 15 ) and geranylgeranyl diphosphate (GGDP,C 20 ), are produced by the activities of Biosynthesis of plant-derived flavor compounds 717 three prenyl transferases.…”
Section: Carbohydrate-derived Flavor Compoundsmentioning
confidence: 99%
“…In plants, both IDP and DMADP are synthesized via two parallel pathways, the mevalonate (MVA) pathway, which is active in the cytosol, and the methylerythritol 4-phosphate (MEP) pathway, which is active in the plastids (Lichtenthaler, 1999;Rodriguez-Concepció n and Boronat, 2002;Rohdich et al, 2002;Rohmer, 2003). It is generally recognized that the cytosolic pathway is responsible for the synthesis of sesquiterpenes, phytosterols and ubiquinone, whereas monoterpenes, gibberellins, abscisic acid, carotenoids and the prenyl moiety of chlorophylls, plastoquinone and tocopherol are produced in plastids (Lichtenthaler, 1999;Rodriguez-Concepció n and Boronat, 2002;Rohdich et al, 2002;Rohmer, 2003), but indications of cross-talk between the plastidic and cytosolic pathways have been found in tobacco, Arabidopsis and snapdragon petals Dudareva et al, 2005;Ohara et al, 2003). The direct precursors of terpenoids, linear geranyl diphosphate (GDP, C 10 ), farnesyl diphosphate (FDP, C 15 ) and geranylgeranyl diphosphate (GGDP,C 20 ), are produced by the activities of Biosynthesis of plant-derived flavor compounds 717 three prenyl transferases.…”
Section: Carbohydrate-derived Flavor Compoundsmentioning
confidence: 99%
“…While most biochemical reactions leading to tocopherol biosynthesis were identified more than two decades ago Soll et al, , 1983Soll et al, , 1985, genes encoding enzymes for tocopherol biosynthesis were identified relatively recently (Shintani and DellaPenna, 1998;Collakova and DellaPenna, 2001;Porfirova et al, 2002;Savidge et al, 2002;Cheng et al, 2003;Rohmer, 2003;Van Eenennaam et al, 2003). Homogentisic acid and phytyldiphosphate (PDP) serve as precursors for tocopherol biosynthesis (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…found in most eubacteria, green algae, and the chloroplasts of higher plants (1,5,6). In the MVA pathway, DMAPP must be generated from IPP by an isopentenyl diphophate/ dimethylallyl diphosphate isomerase (IDI, Scheme 1) (1).…”
mentioning
confidence: 99%